Techno-Economic Feasibility Analysis of a Small-Scale Waste-to-Energy Power Plant as a Supporting Electricity Source: A Case Study on Sabira Island - Harahap, Saskia Saraswati; Garniwa, Iwa (International Journal of Computer and Information System (IJCIS), 2025)
This study explores the techno-economic feasibility of establishing a small-scale waste-to-energy (WTE) power plant using anaerobic digestion technology on Sabira Island, one of the outermost islands of Jakarta, Indonesia. As an isolated area with limited energy access and increasing organic waste generation—estimated at around 1 to 1.2 tons per day—Sabira presents both an environmental challenge and a renewable energy opportunity. Through the conversion of organic waste into biogas, which can then be used to generate electricity, this project seeks to address waste management issues while contributing to sustainable energy production in remote regions. A comprehensive techno-economic analysis was conducted, incorporating factors such as capital and operational costs, biogas yield potential, energy conversion efficiency, and local electricity pricing. Two different electricity selling price scenarios were evaluated to determine financial viability. The results show that under the first pricing scheme, the project fails to meet the minimum return expectations, whereas the second scenario demonstrates acceptable economic performance, suggesting that the project can be considered feasible if more favorable electricity tariffs are adopted. The study concludes that successful implementation of such a WTE system would depend not only on technical and economic parameters but also on supportive policy frameworks, appropriate pricing mechanisms, and access to clean energy financing. The findings offer valuable insights for policymakers and stakeholders aiming to promote decentralized renewable energy solutions in Indonesia’s remote islands.